Making the head: Caspases in life and death - Svandova, Eva; Lesot, Herve; Sharpe, Paul; Matalova, Eva (Frontiers in Cell and Developmental Biology, 2023)
The term apoptosis, as a way of programmed cell death, was coined exactly a half century ago and since its discovery the process has been extensively investigated. The anatomy and physiology of the head are very complex and, for that reason, apoptosis has mostly been followed in separate structures, tissues or cell types. This review aims to provide a comprehensive overview of recent knowledge concerning apoptosis-related molecules involved in the development of structures of head with a particular focus on caspases, cysteine proteases having a key position in apoptotic pathways. Since many classical apoptosis-related molecules, including caspases, are emerging in several non-apoptotic processes, these were also considered in this context. The largest organ of the head region is the brain and its development has been intensely investigated, including the roles of apoptosis and related molecules. Neurogenesis research includes sensory organs such as the eye and ear, efferent nervous system and associated muscles and glands. Caspases have been also associated with normal function of the skin and hair follicles. Regarding mineralised tissues within craniofacial morphogenesis, apoptosis in bones has been of interest along with palate fusion and tooth development. Finally, the role of apoptosis and caspases in angiogenesis, necessary for any tissue/organ development and maintenance/homeostasis, are discussed. Additionally, this review points to abnormalities of development resulting from improper expression/activation of apoptosis-related molecules.